Compulsory English Language Teaching in Taibah University at Undergraduate Level: Problems and Challenges - Ahmad Khan, Waquar (Journal for the Study of English Linguistics, 2021)
Believe it or not, attitude can be an obstacle.To learn any language, positive attitude is prerequisite, and a learner needs to go for it. Learning English as a foreign language is certainly not an easy task. Particularly if you are learning English in a non-English-speaking country. English language teaching and learning always attracts the attention of young minds and young generations across the globe for many pedagogical, sociolinguistic, and economic reasons. The present study focuses on teaching English to the students of Arabic and Islamic studies as their compulsory paper at Taibah University. The research paper is based on action research carried out at Al Ula campus, Taibah University. Compulsory English course specification caters to a mixed and mostly large group of students who belong to different social, cultural, economic, and regional background. It is because of this reason; the primary focus of this study is to find out the problems and challenges among learners and teachers. More precisely, the impact and interference of mother tongue (Arabic), lack of opportunity to use English in day to day activities, approach concerning learning English, and inefficacy of EFL learning and teaching.